Dispositions of In-Service English Teachers towards Developing Pedagogical Competence by Technology Literacy - Rahayu Apriliaswati (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
Technology literacy is a must for living in Industry 4.0 includes English teachers who face millennial students. This study investigated the dispositions of in-service English teachers namely beliefs, enthusiasms, commitments, attitudes, initiatives, responsiveness, strong work ethics, open-mindedness, patience, lifelong learners, adaptations, collaborations, proactive, and reflections towards improving pedagogical competence by applying technology literacy during the PPG workshop especially during constructing lesson plan, simulation, and teaching practice at school. This is a case study of descriptive qualitative research which was conducted at Teacher Education Program (PPG) of Tanjungpura University in Pontianak in 2019. 47 in-service English teachers who were participating in this program were the subject of this study. Data were collected through the distribution of a questionnaire and in-depth interview, as well as classroom observation. Based on the result of data analysis, most of in-service English teachers (88.80%) have positive dispositions towards applying technology literacy. They showed their beliefs,enthusiasms, commitments, attitudes, initiatives, responsiveness, strong work ethics, open-mindedness, patience, lifelong learners, adaptations, collaborations, proactive, and reflections. Almost all of teachers (93,61-100%) had experiences to use technology to develop their pedagogical competence such as selecting techniques for teaching language skills, developing teaching materials, and selecting teaching media. Most of in-service English teachers (80-82%) had skills to use images/pictures, video, you tube. Factors such as digital literacy, infrastructure for internet access are needed by the teachers to use technology to improve their pedagogical competence.